Atmospheric particulate fractions from Nigerian crude oil spillage - Adewole Johnson Adesanmi; Oyetunji Babatunde Okedere; Jacob Ademola Sonibare; Francis Boluwaji Elehinafe; Bamidele Sunday Fakinle (Environmental Challenges, 2021)
Laboratory simulations of the spill behaviors of three different Nigerian crude oil samples over three media (fresh water, sea water and soil) were carried out with a view to determining the effect of crude oil spillage on emission of fine (PM2.5) and inhalable particulates fractions (PM10). The spillage experiments were carried out in an environmental test box fitted with equipment to regulate the micro climatic conditions (temperature and Relative humidity). The maximum concentrations of PM2.5 were 711, 689 and 680 µgm−3 while those of PM10 were 972, 946 and 940 µgm−3 for sample A, B and C respectively. These peak concentrations were obtained for spill conditions corresponding to fresh water at 45 °C and 49% relative humidity. The least concentrations of PM2.5 and PM10 emitted across all samples were 63 µgm−3 and 256 µgm−3 respectively and these corresponded to spillage over sea water at 15 °C and 80% relative humidity. These concentrations clearly exceeded the short time averaging period (24 h) standards set for PM2.5 and PM10 by the United States Environmental Protection Agency. Incessant crude oil spillages in the Nigerian oil fields are therefore predicted to cause degradation of air quality within a short duration from the spill.